Fatigue and bending behaviour of friction stir welded DH36 steel. Issue 9 (June 2016) - Fowler, Steven; Toumpis, Athanasios; Galloway, Alexander
Abstract Friction stir welding presents many advantages over conventional welding techniques; however, there is limited published data with regard to the fatigue and bending performance of friction stir welded steels. Hence, this investigation aims to evaluate friction stir welded DH36 steel subjected to these loading conditions. A comprehensive fatigue and bending programme has been implemented to assess the impact of process-related features, such as weld root flaws, on the welds' performance. Strain gauges located on the top and bottom surfaces of fatigue samples allowed the secondary bending stresses to be quantified when clamped in the fatigue test machine. Bend test samples were completed to a 180° U-bend for as-welded and ground samples. The bend testing programme demonstrated satisfactory performance of friction stir welded DH36 steel. Despite the presence of surface flaws, cracks did not propagate in bending indicating adequate levels of toughness. Fatigue performance was poor in comparison with results from similar welds; however, it was found to be acceptable in terms of class recommendations for fusion welding. This lower performance was predominantly attributed to a weld root flaw. Strain gauge measurements indicated that the local stress at the weld root was up to 25 % lower than the nominal stress determined prior to testing, thus artificially improving fatigue performance. Welds of good quality and refined microstructure were found; however, process-related flaws on the top and bottom surface emphasise the need for optimisation of the tool material and welding parameters.